Evaluation of Green School Implementation in the South Tangerang Region at SMP 9 and SMP Islam Amalina - Valentina Efi Oknasari; Kurniawati Kurniawati; Maria Ariesta Utha (Budapest International Research and Critics University, 2023)
Education is very important in this globalisation era and has even become a basic need for every human being, because by obtaining education humans will be able to improve their quality of life (Amirudin & Muzaki, 2019). Education is also one of the factors supporting the progress of a country. The high level of education in a country can produce quality human resources and take part in developing their country (Rahmawati, Rosita & Asbari, 2022). According to Siregar, (2021) the higher the quality of a country's education, the higher the quality of human resources that can advance and make their country proud. To analyse the Green School Activities at SMPN 9 Tangerang and SMP Islam amalina Tangerang Selatan in South Tangerang and to analyse the Implementation of Education for Sustainable Development at SMPN 9 Tangerang and SMP Islam amalina Tangerang Selatan in implementing the sustainable development program. This study uses a qualitative approach to analyse the role of schools in Green School in terms of the implementation of education for sustainable development in Green School as well as the issues and strategies applied. The subjects of this study were SMPN 9 South Tangerang and SMP Islam amalina South Tangerang. The respondents of the survey were the Principal, Vice Principal and Teachers and staff who have worked in the school. Based on the analysis of the implementation of education for sustainable development on the governance of Adiwitaya Junior High School at SMPN 9 Tangerang and SMP Islam amalina South Tangerang, the governance carried out by the school is currently still less than optimal and many are not in accordance with the vision and mission that has been proclaimed and set by the green school programme so that many must be improved and evaluated to support the sustainability of the green school programme. To improve innovation performance, schools must be more proactive in responding to various issues related to changes in the school environment both internally and externally. These changes must be responded wisely through research and development activities so that schools can maintain their existence in the future. One of the things that need to be considered is related to governance in the implementation of Green School. Limitations Of Research - The research only discusses the Evaluation of Green School Implementation at SMP 9 South Tangerang and SMP Islam Amalina and how far the current Green School implementation and implementation is so that it can find out the challenges in implementing Green School and provide strategies for its evaluation. So that the target to achieve sustainable development can be realised.